The Islands : Six Fictions - Wall, William, 1955- (Project Muse, 2017)
In this collection of interconnected stories, the beautiful and ravaging forces of sea and land collide with the forces of human nature, through isolation and family, love and loss, madness and revelation. The stories follow the lives of two sisters and the people who come and go in their lives, much like the tides. Dominated by the tragic loss of a third sister at a young age, their family spirals out of control. We witness three stages of the sisters' lives, each taking place on an island--in southwest Ireland, southern England, and the Bay of Naples. Beautifully and sparsely written, the stories deeply evoke landscape and character, and are suffused with a keen eye for detail and metaphor.